Compositional Changes in Potato Carbohydrates and Polyphenols during In vitro Gastrointestinal Digestion. (3rd July 2022) - Thakur, Nitasha; Raigond, Pinky; Jayanty, Sastry S.; Goel, Gunjan; Dutt, Som; Singh, Brajesh
Abstract: Effect of processing method on in vitro bioaccessibility of carbohydrates and polyphenolics is investigated using three Indian potato varieties. Results show that boiling and microwaving breakdown the starch to maximum extent (up to 98%). Bioaccessibility of reducing sugars was 10‐times and 13‐times high, and sucrose was 2‐times and 4‐times higher with boiled and microwaved potatoes, respectively compared to undigested forms. Boiling and microwaving significantly decreases the polyphenolics by 26% and 10%, respectively. Though boiling significantly decreased the concentration of chlorogenic acid (29%), caffeic acid (20%) andrutin (6%), microwaving significantly increased chlorogenic acid (3‐fold), caffeic acid (3.4‐fold) and rutin (1.7‐fold). Polyphenolics (41 mg/100 g FW), chlorogenic acid (251 µg/g FW), caffeic acid (58 µg/g FW) and sugars are most bioaccessible from microwaved potatoes; and rutin (20 µg/g FW) from boiled potatoes. Principal component analysis indicates that microwaving releases more polyphenolics. Hence microwaving can be recommended as the best cooking method, though high sugar bioaccessibility also needs to be kept in mind. The study indicates that during bioaccessibility studies of phytonutrients in starchy foods, carbohydrate bioaccessibility should not be ignored. The finding of this study needs to be confirmed through cell uptake model and through in vivo studies to further conclude the present results. Abstract : Microwaving enhances the bioaccessibility of total and individual polyphenolics. However concomitant high release of sugars due to more starch hydrolysis in the intestinal phase is of major concern. The study indicates that during bioaccessibility studies of phytonutrients in starchy foods, carbohydrate bioaccessibility should not be ignored.